The Influence of Unemployment, Human Development Index and Poverty on Economic Growth in North Sulawesi 2008-2022 - Chelsi J. Sengkey; Amran T. Naukoko (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to look at the influence of unemployment, human development index and poverty on economic growth in North Sulawesi Province in 2008-2022. The data used is secondary data from the North Sulawesi Central Statistics Agency. The analysis technique used is multiple linear regression with the help of Eviews 12 software. The results of this research show that the Unemployment Rate variable has a negative and insignificant effect on economic growth. The Human Development Index has a negative and significant effect on economic growth. Poverty level has a positive and insignificant effect on economic growth. The results of this research show that the Unemployment Rate, Human Development Index and Poverty Rate have a significant relationship to economic growth in North Sulawesi Province in 2008-2022.